CONDITION OF PERIPHERAL NERVE RATS UNDER MICROMERCURIALISM IN THE EARLY STAGES AFTER INJURY - Шамало, С.М. (World of Medicine and Biology, 2015)
Recovery of peripheral innervation disorders caused by trauma, do not always lead to satisfactory results. This is due to lack fundamental knowledge about the mechanisms of regeneration of peripheral nerve fibers, the role of the microenvironment and trophic factors. Therefore, it remains the search for new pharmacological agents which have a positive effect on recovery processes.The aim of this study was to examine the state of the injured nerve trunk rats under the influence of small doses of mercury and to investigate the effect on recovery processes Thiotriazoline nerve. In experiments on white rats, which were divided into 4 groups, recreated the standard model of sciatic nerve injury in conditions of chronic subhronichnoho micromercurialism. Postoperatively, the rats of the first and third groups pharmacotherapy not performed, and the second and fourth groups of animals were injected intraperitoneally daily for 2 weeks, Thiotriazoline solution at a dose of 100 mg / kg. The material for the study were distal damaged rat sciatic nerve after 3 weeks of playing standard model of peripheral nerve injury in conditions of chronic subhronichnoho micromercurialism. Material recorded 2.5% glutaraldehyde in phosphate buffer and treated by the standard electron microscope method. Sections nerves were made on ultratomi LKV-III. Ultra thin sections prodyvlyalys and photographed in the electron microscope PEM-125K.Our research shows that thiotriazolin activates metabolism and biosynthesis neyrolemotsytiv and fibroblasts and thereby accelerates the neuroticism peripheral segment.Our research has shown that even small doses of mercury adversely affect regeneration. A deep violation of all the constituents of nerve fibers and cause a significant delay in the recovery process. However thiotriazolin recovery stimulates nerve trunk, because the drug activates metabolism and biosynthesis. Manifestation of action is to restore organelles neyrolemotsytiv and fibroblasts, which leads to accelerate the process of neuroticism peripheral segment, accelerating the process of myelination and disaster degeneration.
Keywords: mikromerkurialism; sciatic nerve; regeneration; thiotriasolin